Health-Related Quality of Life of COPD Patients Attending Outpatient Clinic at Institute of Respiratory Medicine, Kuala Lumpur, Malaysia - J, Maria; CM, Aslinda; AR , Nurul Ain; TM, Fatim (IIUM Medical Journal Malaysia, 2010)
Introduction: This study measured the health-related quality of life (HRQoL) among COPD patients attending outpatient clinic at Institute of Respiratory Medicine, Kuala Lumpur. Materials and Methods: A crosssectional survey was conducted from November 2008 to January 2009 on 99 COPD patients. Subjects were interviewed through socio-demographic and health characteristics. The HRQoL was measured using the SF36v2 questionnaires. Results: Majority of the subjects were above 60 years (64.6%) with mean age of 64.10 ± 11.04 years, male (84.8%), Malays (49.5%), married (74.7%), primary educational level (57.6%), income level below RM1000 (39.4%), ex-smoker (64.6%), moderate COPD (40.4%), 1 to 5 years of illness (62.6%), presence of co-morbidities (65.7%) and satisﬁed with support from caregiver (48.5%). The total mean score for physical health component summary (PCS) was 41.64 ± 7.99 and mental health component summary (MCS) was 46.53 ± 13.21. Conclusion: There were signiﬁcant differences in PCS for different educational level (p<0.05) and socio-economic status (p<0.01). The MCS were signiﬁcantly different between ethnicity (p<0.05) and level of satisfaction with support from caregiver (p<0.01). This ﬁnding provides information that needed focus in healthcare services.